Detecting and Restoring Gaps Among Forest Patches: AN Achievable and Replicable Proposal to Boost the Landscape Connectivity - Bortoleto, Ludmila Araujo; Rodgers, John; Silva, Alexandre Marko da (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It is well known that one of the main impacts caused by land cover change is the process of forest fragmentation. Connecting the remaining fragments is always an exercise for technicians and academics, and even corridors of remaining vegetation usually present places of forest discontinuity, lacking connection strategies for the corridor to gain a real function.
Keywords: ecological connectivity; connector selection methods; ecological connectors; matrix permeability; wildlife corridors